Quality of Life among Adult Samples: Does Perceived Social Support and Health-Seeking Behavior Counts? - Roberts, Enyelunekpo R.; Owoh, Ucheawaji J.; Atunwa, Sunday A.; Uye, Emmanuel E. (Faculty of Psychology, Universitas Semarang, 2025)
All human activities are geared towards making life more meaningful, and the desire to improve the quality of life has been taken as a fundamental and universal human drive. Studies that investigated quality of life using different predictors have produced varying results. Therefore, the objective of this study was to examine the predictive ability of perceived social support and health-seeking behavior on quality of life among the adult population in Port Harcourt. A cross-sectional survey design was adopted, and the study population was selected using a purposive sampling technique. A convenience sampling technique was used to select 254 participants using validated questionnaires. Data were analyzed using multiple regression analysis to test one hypothesis and were accepted at a p < .05 level of significance. The results demonstrated that perceived social support and health-seeking behavior jointly predicted quality of life among study participants [R² = .19, F(2, 252) = 5.956, p < .05], indicating a significant effect on quality of life. The implication of this finding is a wake-up call to public health professionals, community stakeholders, and urban healthcare development authorities to provide social support through empowerment programs and create centers where individuals can access information on health-seeking behavior, thereby improving their quality of life.